Epigenetic Alteration Shaped by the Environmental Chemical Bisphenol A - Qin, Tengfei; Zhang, Xiaoping; Guo, Ting; Yang, Ting; Gao, Yahui; Hao, Wei; Xiao, XiangFen (Frontiers in Genetics, 2021)
Bisphenol A (BPA) is extensively used in plastic products and epoxy resins. Epigenetic response to the environmental chemical BPA was involved in multiple dysfunctional categories such as cancer, reproductive system, metabolism, pubertal development, peripheral arterial disease, infant and childhood growth, and neurodevelopment outcomes. In this review, we described the recent progress of the epigenetic effects of the environmental chemical BPA including DNA methylation and histone methylation. The DNA methylation accompanied by the transcriptional change of key genes affected by the BPA exposure was related to the neural development, production, metabolism disorders and cancer pathways. In addition, BPA could also affect the histone modification of H3K27me3, H3K9ac and H3K36me3. Last, we reviewed the recent studies of the toxic-epigenomics approach to study the epigenetic effect of BPA exposure genome-wide.